ENTREPRENEURSHIP AND DIGITAL LITERACY TRAINING PROGRAM TO PROMOTE TOURISM FOR POKDARWIS IN MENTAWAI ISLANDS : A CASE STUDY OF MUNTEI VILLAGE - Indra Kurniawan Rezki; Ganefri; Asmar Yulastri; Wakhinuddin; Mukhlidi Muskhir; Asrul Hudai (EDU RESEARCH, 2024)
Mentawai is a regency located in West Sumatra, Indonesia, known for its natural beauty and cultural richness, particularly in marine and cultural tourism. Muntei Village, in the South Siberut Subdistrict, is a prime example of this potential, offering diverse tourism experiences and cultural heritage. However, the local Tourism Awareness Groups (POKDARWIS) face challenges due to limited digital literacy, which hinders effective tourism promotion. This study details a program designed to enhance the digital literacy of POKDARWIS members through structured training and assistance. Key findings reveal significant improvements in digital skills, including website creation, social media engagement, and content creation for tourism promotion. These developments highlight the importance of digital literacy in supporting sustainable tourism and economic growth in the Mentawai Islands.